Emergência psiquiátrica no hospital geral : prevalência do uso de benzodiazepínicos em idosos e não idosos e suas associações - Nogueira, Eduardo Lopes (2012)
The aging process is a worldwide phenomenon that occurs more rapidly in developing countries like Brazil. Even if the effects of aging have not been adequately measured at emergencies, is well documented that aged people are more likely to need health assistance and use various medications, among these, psychotropic. This panorama is more pronounced when these individuals shows mental health impairment. The scientific background indicates that the high prevalence of psychotropic use in the elderly is due to inappropriate prescribing and non medical use combined with higher chronicity rates, abuse or dependence related to subgroups of these drugs, especially benzodiazepines. This study investigated the prevalence and characteristics associated with current use of benzodiazepines in a sample of patients evaluated by a psychiatric consultation at emergency setting. The results showed very high frequency of benzodiazepines use among elderly patients. Another important result showed that benzodiazepines were the most common class of drugs indicated by psychiatrists on duty. In the total sample (N:1113), just over half of the elderly (≥65 years), 44.0% of the middle-aged group (45-64 years) and 33.6% of the younger adults (18-44 years) were regular users of benzodiazepines (p<0.001). Using Poisson regression to estimate prevalence ratios (PR), benzodiazepine use was independently associated with increasing age: RP=1.261 for the group of 35-49 years (p = 0.024), PR=1.400 for group of 50-64 years (p=0.007), PR=1.699 for the group of 65-79 years (p<0.001); for the age group of 80 years or more show PR of 1.343 but not reach statistical significance (p=0.387). Other significant independent associations were found for personality disorder (PR=1.465, p=0.004), presence of non-psychiatric medical comorbidity (PR=1.290, p=0.006) and suicide risk (PR=1.200, p=0.032). It´s important to emphasize that such evidence should be replicated and refined in other emergency rooms of general hospitals, psychiatric emergencies and admission services considering that these factors do not justify the use of this class of psychotropic drugs. The high prevalence of benzodiazepine use in emergencies detected in this study is worrisome, especially for the elderly, since the emergencies of general hospitals provide a vital assistance to the population and are sometimes the first opportunity to receive mental health care for a considerable number of individuals. Other controlled studies should be conducted on emergency samples because works that may produce robust results in this context are rare, but critical to improve knowledge in the field of emergency medicine.